Antiproliferative Potential of Extracts from Kappaphycus Seaweeds on HeLa Cancer Cell Lines - Tiek, Ying Lau; Delbora Fenny Vittal; Cassandra Yii Chew, Sze; Wilson Lym Yong, Thau (Universiti Kebangsaan Malaysia, 2014)
A review of the current literature indicates that natural seaweeds are an excellent source of bioactive compounds with antioxidant, antimicrobial and antitumor properties. In the present study, 90% methanolic, 70% acetonic and aqueous extracts from Kappaphycus alvarezii (strains Crocodile, Giant and Brown) and Kappaphycus striatum were used to inhibit the growth of HeLa cell lines. MTS assay was carried out to determine the proliferation of HeLa cells in the presence of different seaweed extracts. Both 500 μg/mL of aqueous and methanolic extracts from K. striatum demonstrated highest anti-proliferative activity against HeLa cells with cell growth inhibition of 53.5 and 43.7%, respectively. Treatment with the aqueous extracts from three strains of K. alvarezii did not show any growth inhibition against HeLa cell lines. The acetonic extract of Kappaphycus seaweeds exhibited a very poor cell growth inhibition with inhibitory activity observed under the treatment of 300 to 500 μg/mL of K. alvarezii strain Brown only. Further studies are suggested to identify and purify the specific anti-tumoral compounds for potential use in cancer therapy.